The effect of problem-based learning on the critical thinking of students in the intellectual and ethical development unit - Semerci, Nuriye (Soc Personality Res Inc, 2006)
The aim in this study was to determine the effect of problem-based learning (PBL) on the critical thinking of students in the Development and Learning course in the Intellectual and Ethical Development Unit. The experimental model with a pretest-posttest control group was used with 60 students. The experimental group continued for 4 weeks and the students were provided with sample events which included problems, and they were asked to find the necessary information by themselves while explaining these events. In the control group, traditional methods of teaching (expression, question-answer) were used. Scale data were collected with the Critical Thinking Scale (Semerci, 2000). The KMO (Kaiser-Meyer-Olkin) value of the scale is 0.75 and Cronbach alpha coefficient is 0.90. The experimental group was more successful.
Keywords: problem-based learning; critical thinking; problem solving; development; learning